Modelling the lactate response to short-term all out exercise - Beneke, R.; Jumah, M. D.; Leithäuser, R. M. (Journal of the International Society of Sports Nutrition, 2007)
The maximum post exercise blood lactate concentration (BLCmax) has been positively correlated with maximal short-term exercise (MSE) performance. However, the moment when BLCmax occurs (TBLCmax) is rather unpredictable and interpretation of BLC response to MSE is therefore difficult.